Law Enforcement Against Cyber Crimes in Indonesia: Analysis of the Role of the ITE Law in Handling Cyber Crimes - Waluyadi, Waluyadi (Politeknik Siber Cerdika Internasional, 2024)
Cybercrime in Indonesia is increasing along with the development of information technology. The Electronic Information and Transactions Law (UU ITE) is present as the main legal instrument to regulate and overcome various forms of cybercrime. However, the implementation and enforcement of laws related to the ITE Law are still controversial, especially in handling cases involving privacy, defamation , and hate speech in the digital space. This study examines the effectiveness of the ITE Law in enforcing laws related to cybercrime in Indonesia. This study aims to analyze the role and effectiveness of the ITE Law in combating cybercrime in Indonesia, as well as identifying the challenges faced in the law enforcement process. The research method used is normative juridical with a qualitative approach. Data were collected through literature studies that include analysis of laws, government regulations, and case studies of cyber crimes that have been legally processed in Indonesia. This study found that although the ITE Law has become an important basis for law enforcement against cybercrime, there are still weaknesses in its implementation, such as a lack of understanding of the law by law enforcers and ambiguity in the application of related articles. Several cases show that the ITE Law can be misused, so better legal reform and harmonization are needed to effectively address cybercrime.